Arabic script language identifications using adaptive neural network - Ali Selamat, author; Ng, Choon Ching, 1984-, author; IASTED International Conference on Advances in Computer Science and Technology (4th: 2008: Kedah) (Skudai : Universiti Teknologi Malaysia, 2008)
PRZSL